Antibiotic prescriptions rates for acute respiratory tract infections in the United States ambulatory settings, 1995–2006 - Grijalva, Carlos G. (JAMA, 2009)
CONTEXT: During the 1990s, antibiotic prescriptions for acute respiratory tract infections (ARTI) declined in the United States. The sustainability of those changes is unknown. OBJECTIVE: To assess trends in antibiotic prescriptions for ARTI DESIGN, SETTING AND PARTICIPANTS: National Ambulatory Medical Care Survey and National Hospital Ambulatory Medical Care Survey data (1995–2006) were used to examine trends in antibiotic prescription rates by antibiotic indication and class. Annual survey data and census denominators were combined in 2-year intervals for rate calculations. MAIN OUTCOME: National annual visit and antibiotic prescription rates for ARTI including otitis media (OM) and for non-ARTI. RESULTS: Among children aged <5 years, annual ARTI visit rates declined 17% (95% CI: 9–24) from 1883 per 1000 population in 1995–1996 to 1560 per 1000 in 2005–2006, primarily due to a 33% (95% CI: 22–43) decline in OM visit rates (from 950 to 634 per 1000, respectively). This decline was accompanied by a 36% (95% CI: 26–45) decline in ARTI-associated antibiotic prescriptions (from 1216 to 779 per 1000). Among persons aged ≥5 years, ARTI visit rates remained stable but associated antibiotic prescription rates declined by 18% (95% CI: 6–29), from 178 to 146 per 1000. Antibiotic prescription rates for non-OM ARTI for which antibiotics are rarely indicated declined by 41% (95% CI: 22–55) and 24% (95% CI: 10–37) among persons aged <5 and ≥5 years, respectively. Overall, ARTI-associated prescription rates for penicillin, cephalosporins, sulfonamides and tetracyclines declined. Prescription rates for azithromycin increased and it became the most commonly prescribed macrolide for ARTI and OM (10% of OM visits). Among adults, quinolone prescriptions increased. CONCLUSION: Overall antibiotic prescription rates for ARTI declined, associated with fewer OM visits in children aged <5 years and with fewer prescriptions for ARTI for which antibiotics are rarely indicated. However, prescription rates for broad spectrum antibiotics increased significantly.